Follow the leader? Where to for the National Dialogue process? - Ehrenreich, Tony (New Agenda: SA Journal of Social and Economic Policy, 2026)
Despite decades of colonialism, land dispossession, apartheid exploitation, and protracted armed struggle, South Africans are willing to talk to each other; negotiation is a hallmark of our post-apartheid society. Now that’s being put to the test. The National Dialogue was mandated to confront the intractable triple crisis of unemployment, poverty and inequality, but it faces another challenge from deep within the party that created it. TONY EHRENREICH asks if the ANC leadership, crippled by corruption and greed, is still up to negotiating a way to a better future.